Coastal Inundation Adaptive Strategy in Semarang Coastal Area - Suhelmi, Ifan Ridlo; Triwibowo, Hariyanto (Universitas Muhammadiyah Surakarta, 2018)
Semarang Coastal has a high level of vulnerability to inundation, river flooding and tidal flooding. To solve the problems, a region has an adaptive capacity to the phenomena encountered. The aims of study to map the level of vulnerability and adaptive capacity of the region in facing the phenomenon and provide an alternative strategy in facing the impact of inundation in coastal areas. Based on capacity index and vulnerability index in 2015, most urban villages are located in quadrant 3 (58 villages), in quadrant 1 (36 villages) and quadrant 4 (5 villages). the results showed that most of villages located at coastal areas had a high vulnerability with low adaptive capacity. Considering spatial planning (RTRW) for 2030, population density changes, Semarang City Facility health facilities Plan in 2030, and the open areas as defined in the Semarang 2011-2030 spatial plan (RTRW) a major shift towards the quadrant 2 was observed, suggesting an increased capacity to encountered inundation susceptibility.